Avoiding Radical Surgery in Elderly Patients With Rectal Cancer Is Cost-Effective. Issue 1 (January 2017) - Rao, Christopher; Sun Myint, Arthur; Athanasiou, Thanos; Faiz, Omar; Martin, Antony Paul; Collins, Brendan; Smith, Fraser McLean
Abstract : BACKGROUND: Radical surgery is associated with significant perioperative mortality in elderly and comorbid populations. Emerging data suggest for patients with a clinical complete response after neoadjuvant chemoradiotherapy that a watch-and-wait approach may provide equivalent survival and oncological outcomes. OBJECTIVE: The purpose of this study was to compare the cost-effectiveness of watch and wait and radical surgery for patients with rectal cancer after a clinical complete response following chemoradiotherapy. DESIGN: Decision analytical modeling and a Markov simulation were used to model long-term costs, quality-adjusted life-years, and cost-effectiveness after watch and wait and radical surgery. Sensitivity analysis was used to investigate the effect of uncertainty in model parameters. SETTINGS: A third-party payer perspective was adopted. PATIENTS: Patients included in the study were a 60-year–old male cohort with no comorbidities, 80-year–old male cohorts with no comorbidities, and 80-year–old male cohorts with significant comorbidities. INTERVENTIONS: Radical surgery and watch-and-wait approaches were studied. MAIN OUTCOME MEASURES: Incremental cost, effectiveness, and cost-effectiveness ratio over the entire lifetime of the hypothetical patient cohorts were measured. RESULTS: Watch and wait was more effective (60-year–old male cohort with no comorbidities = 0.63 quality-adjusted life-years (95% CI, 2.48–3.65 quality-adjusted life-years); 80-year–old male cohort with no comorbidities = 0.56 quality-adjusted life-years (95% CI, 0.52–1.59 quality-adjusted life-years); 80-year–old male cohort with significant comorbidities = 0.72 quality-adjusted life-years (95% CI, 0.34–1.76 quality-adjusted life-years)) and less costly (60-year–old male cohort with no comorbidities = $11, 332.35 (95% CI, $668.50–$23, 970.20); 80-year–old male cohort with no comorbidities = $8783.93 (95% CI, $2504.26–$21, 900.66); 80-year–old male cohort with significant comorbidities = $10, 206.01 (95% CI, $2762.014–$24, 135.31)) independent of patient cohort age and comorbidity. Consequently, watch and wait was more cost-effective with a high degree of certainty (range, 69.6%–89.2%) at a threshold of $50, 000/quality-adjusted life-year. LIMITATIONS: Long-term outcomes were derived from modeled cohorts. Analysis was performed for a United Kingdom third-party payer perspective, limiting generalizability to other healthcare contexts. CONCLUSIONS: Watch and wait is likely to be cost-effective compared with radical surgery. These findings strongly support the discussion of organ-preserving strategies with suitable patients.